2006
DOI: 10.1002/j.2168-9830.2006.tb00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaving Engineering: Lessons from Rowan University's College of Engineering

Abstract: The paper focuses on retention in the Rowan University undergraduate engineering program with many “female‐friendly” features despite its design as best practices for all students. Both male and female “stayers” in the program are compared to “leavers” on a variety of characteristics, including pre‐college and family background, grades, satisfaction with the Rowan program, engineering self‐confidence, and future expectations about their engineering major and career. Data come from a special survey of all Rowan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
77
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 5 publications
3
77
0
Order By: Relevance
“…These factors include pre-entry characteristics such as skills and abilities 10,11 family background 12 , institutional experiences 13,14 , and finances 15 . While research in college retention has focused on integration into the university, research in engineering retention has focused more on integration into the engineering culture 16 .…”
Section: Introductionmentioning
confidence: 99%
“…These factors include pre-entry characteristics such as skills and abilities 10,11 family background 12 , institutional experiences 13,14 , and finances 15 . While research in college retention has focused on integration into the university, research in engineering retention has focused more on integration into the engineering culture 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Not only is middle school a critical time for all students to start thinking about their future and make the appropriate academic choices, it is particularly important for young girls because until the high school years girls and boys do not differ much in technical abilities years but rather in their attitudes toward technological careers like engineering [40][41] . By the time some girls reach high school they begin underestimating their own technical abilities and start placing more importance on being popular rather than academic performance [42][43] .…”
Section: Introductionmentioning
confidence: 99%
“…The concerns of low numbers of women in STEM have led to studies on the attrition 1 and the implementations of programs for the female students 2 . Studies found that students who withdraw from STEM majors are less involved in extra-curricular engineering activities, have lower engineering self-efficacy and career expectations, but higher anxiety 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that students who withdraw from STEM majors are less involved in extra-curricular engineering activities, have lower engineering self-efficacy and career expectations, but higher anxiety 1,3 . However, the average GPA of women who withdraw from STEM is no different than that of others 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation